3(p+q)=p
Question ID
2097114
Created
September 18, 2023 11:27pm UTC
Rating
0
URL
https://questions.llc/questions/2097114
Answers
1
Views
3
1 answer

Here is the solution for the equation:
3(p + q) = p
First, distribute the 3 on the left side:
3p + 3q = p
Next, subtract p from both sides to isolate the variable terms:
3q = 2p
Finally, divide both sides by 3 to solve for q:
q = (2p)/3
Therefore, the solution for the equation 3(p + q) = p is q = (2p)/3.Answer ID
2947104Created
September 18, 2023 11:27pm UTCRating
0